Kinetics of Oxidation of 4-Oxoacids by N-Chlorosaccharin in Aqueous Acetic Acid Medium - MOHAMED FAROOK, N.A. (Asian Journal of Chemistry, 2010)
Kinetics of oxidation of substituted and unsubstituted 4-oxoacids (S) by N-chlorosaccharin (NCSA) in aqueous acetic acid medium have been studied. The reaction follows first-order kinetics, each in 4-oxoacids, NCSA and H+. The effect of changes in the electronic nature of the substrate reveals that there is a development of positive charge in the transition state. On the basis of the kinetic results and product analysis, a suitable mechanism has been proposed for the reaction of NCSA with 4-oxoacids.